Effect of Nilitis® SR on Knee Pain in Japanese Adults: A Double-Blind, Randomized, Placebo-Controlled Study - Majeed, Muhammed; Vaidyanathan, Priti; Natarajan, Sankaran; Majeed, Shaheen; Vuppala, Kiran Kumar (International Journal of Innovative Research in Medical Science, 2016)
Objectives: The mitigation of knee pain leads to improved quality of life (QOL). NiLitis® SR is a dietary supplement containing Boswellin® Super (Boswellia serrata extract), Curcumin C3 Complex® (turmeric extract) and ginger extract, which is hypothesized to have an anti-inflammatory effect. This study examined the effect of NiLitis® SR on knee pain in healthy Japanese adults. Methods: This was a double-blind, randomized placebo-controlled trial, comparing the ingestion of NiLitis® SR as against placebo over an 8-week period. In-hospital inspections were carried out three times, i.e., at 0 week, 4 weeks and 8 weeks. The primary outcome measure was the Japanese Knee Osteoarthritis Measure (JKOM). Secondary outcome measures were Visual Analog Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), serum hyaluronic acid (sero-HA), serum high sensitivity C-reactive protein (hs-CRP) and questionnaires (using Likert scale for Quality of Life). Results: In the NiLitis® SR group, VAS, JKOM total score and WOMAC total score significantly decreased at the end of 8 weeks. Compared with the placebo group, subjects in the NiLitis® group showed significantly lower values in VAS and sero- hyaluronic acid. Conclusion: Intake of NiLitis® SR relieves knee pain and may control hyaluronic acid outflow into the bloodstream.